1987
DOI: 10.1037/h0080012
|View full text |Cite
|
Sign up to set email alerts
|

Acute exercise combined with imaginal exposure as a technique for anxiety reduction.

Abstract: The potential of physical exertion to enhance anxiety reduction was investigated by combining acute exercise with an imaginal exposure treatment for public speaking anxiety. Self-report, behavioural, and psychophysiological outcome measures all indicated that groups that received imaginal exposure improved more than those that received control procedures. The addition of acute exercise increased the treatment effect on two self-report measures (one for females only), although there was an indication of interfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Exercise as an adjunct to enhanced imagery was studied by Schwartz and Kaloupek[77] for anxiety reduction. It was Bruning and Frew[78] who found exercise to be beneficial for stress management and Puetz et al ,[79] found chronic exercise to influence feeling of energy and fatigue, and recently Chafin et al ,[80] found exercise as an effective strategy for anger control.…”
Section: Evidence For Physical Therapy In Palliative Carementioning
confidence: 99%
See 1 more Smart Citation
“…Exercise as an adjunct to enhanced imagery was studied by Schwartz and Kaloupek[77] for anxiety reduction. It was Bruning and Frew[78] who found exercise to be beneficial for stress management and Puetz et al ,[79] found chronic exercise to influence feeling of energy and fatigue, and recently Chafin et al ,[80] found exercise as an effective strategy for anger control.…”
Section: Evidence For Physical Therapy In Palliative Carementioning
confidence: 99%
“…Exercise therapy programs such as aerobic exercise training was shown by McCann and Holmes[ 74 ] to positively influence depression, followed by Brown and Siegel,[ 75 ] who studied adolescent population and later McNeil et al ,[ 76 ] confirmed this with added effects of exercise on anxiety. Exercise as an adjunct to enhanced imagery was studied by Schwartz and Kaloupek[ 77 ] for anxiety reduction. It was Bruning and Frew[ 78 ] who found exercise to be beneficial for stress management and Puetz et al ,[ 79 ] found chronic exercise to influence feeling of energy and fatigue, and recently Chafin et al ,[ 80 ] found exercise as an effective strategy for anger control.…”
Section: Evidence For Physical Therapy In Palliative Carementioning
confidence: 99%
“…These results are not surprising in light of the positive findings shown for hypothesis #1, and previously conducted research comparing exercise and therapy for the treatment of anxiety. Only a limited number of studies in the literature have sought to compare exercise and a more traditional therapeutic intervention for treating anxiety or stress (Long, 1983(Long, , 1984Schwartz & Kaloupek, 1987;Stern, Gorman, & Kaslow, 1983). These researchers reported that both state and trait anxiety were significantly reduced when compared to no-treatment controls.…”
Section: Exercise Vs Group Therapymentioning
confidence: 99%
“…However, other researchers have found additive effects of exercise and therapy with different types of anxiety, and with different populations. For example, Schwartz and Kaloupek (1987) found that subjects who participated in both aerobic exercise (stationary bicycle) and cognitive therapy (imaginal exposure) reported a greater reduction in public speaking anxiety than those involved in cognitive therapy alone. It Downloaded by [Florida State University] at 03:37 05 January 2015 appears that while more treatment may not always translate into more effective treatment, there are circumstances in which exercise can facilitate the therapeutic process, and lead to greater reductions in psychological discomfort.…”
Section: Combined Treatment Vs Individual Treatmentmentioning
confidence: 99%
See 1 more Smart Citation